ENHANCING THE INTERNATIONAL COMPETITIVENESS OF INDONESIAN FOOD AND BEVERAGE INDUSTRY THROUGH FACILITATING THE ADOPTION OF QUALITY ASSURANCE PROGRAMS - agus - sudibyo; Aslam Hasan (JURNAL STANDARDISASI, 2016)
A survey of 102 small to medium sized food processors and manufactures in DKI, West Jawa and Banten province, Indonesia  has been conducted for to know the quality assurance (QA) program. The survey was carried out with method to identify and to distribute a questionnaire and also to interview to small and medium scale food industry respondents selected that develope the QA program. The results of the study reveals that the main reasons for implementing one or more quality assurance (QA) programs in the food business were satisfy/meet customers requirements, to seek the highest standard of quality and food safety, provide cotinous quality control and maintenance, reduce legal liability, improve the business structure, facilitatenew market entry and/or to expand market size and sales.  Conversely, the main reasons for not implementing one or more QA programs were :  the cost of QA implementation and maintenance of QA programs to high, there was no need or no legal requirement to implement QA, the businees was too small.  There was insufficient time, a lack of information or lack of resources. The failure to implement QA systems has the potential to exclude small and medium sized food processors and manufactures from many domestic and international markets.